2020
DOI: 10.3390/nu12030619
|View full text |Cite
|
Sign up to set email alerts
|

Relative Validity and Reproducibility of a Short Food Frequency Questionnaire to Assess Nutrient Intakes of New Zealand Adults

Abstract: There is no recent validated short food frequency questionnaire (FFQ) for use in New Zealand (NZ) adults. This study aimed to evaluate the relative validity and reproducibility of a short FFQ in free-living NZ adults aged 30–59 years. A 57-item, semi-quantitative FFQ was developed and pre-tested. During a 12-month study period the FFQ was administrated twice with a 9-month interval between administrations. Four two-day diet records were collected at months 0, 3, 6, and 9 and a blood sample was taken at month 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
7
18
0
Order By: Relevance
“…An overview of the retrieved studies assessing the reproducibility of FFQs is presented in Table 1 (detail information shown in Supplemental Table 1 ). Of the 123 articles included [ 4 , 10 13 , 15 18 , 20 , 21 , 23 134 ], two articles analyzed differences in different age groups [ 50 , 113 ], and five articles assessed the differences in reproducibility according to time intervals between repeated FFQs [ 39 , 91 , 96 , 113 , 134 ]. The extracted information on characteristics of the included studies is summarized in Table 1 (detail information shown in Supplemental Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the retrieved studies assessing the reproducibility of FFQs is presented in Table 1 (detail information shown in Supplemental Table 1 ). Of the 123 articles included [ 4 , 10 13 , 15 18 , 20 , 21 , 23 134 ], two articles analyzed differences in different age groups [ 50 , 113 ], and five articles assessed the differences in reproducibility according to time intervals between repeated FFQs [ 39 , 91 , 96 , 113 , 134 ]. The extracted information on characteristics of the included studies is summarized in Table 1 (detail information shown in Supplemental Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that the ICCs of an FFQ comprising 255 items ranged from 0.69 (fat) to 0.84 (vitamin A) in Moroccan adults [ 19 ]. A shorter FFQ assessing the average consumption of 57 food items was reported to have a reliability coefficient ranging from 0.56 to 0.70 [ 20 ]. Therefore, FFQ items may induce differences in reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Our sole reliance on maternal self-report of dietary intake and infant feeding behaviour, as opposed to observed measures of data collection, may have introduced recall and social desirability bias [53][54][55] . However, the FFQ we used was shown to have acceptable to good validity when compared to the 8-day dietary record 56 , and dietary patterns derived from PCA and food records are reported to be similar [57][58][59] . Additionally, PCA is inherently subjective, with a tendency towards interpretation bias 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…Data on food consumption was collected from study participants via a self-administered, 1-month recall, FFQ at 36 weeks' gestation. The FFQ was a customized version of the 163-item semi-quantitative FFQ developed by Willett 63 , with changes made to reflect local dietary habits www.nature.com/scientificreports/ as per the nationally-representative nutrition survey available at the time 64 , and further informed by two focus groups of 21 adults aged 30-59 years in New Zealand 56 . The questionnaire comprised 65 questions, of which 57 were grouped as dairy, eggs and meat, fish and seafood, bread, cereals and starches, fruits, vegetables, fast foods, beverages, sweets, baked goods, and miscellaneous ( Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation